Strategi Pendidikan Islam Mengantisipasi Postmodernisme - Anwar, Khairil (Al-Riwayah : Jurnal Kependidikan, 2017)
The issue of education is actually the prone problem in Indonesia. An erroneous education can cause failure in life forever. For example, the term misguided shows that something untoward has happened because of wrong education. It means that fate of a person has a dependency with the education that he or she passed. In the case, there are no parents or students themselves who wanted himself, their progeny or generations they become weak generation. God also reminds us, we must not abandon the weak generation. It is accordance with education expert’s opinion. He said that education save an incredible power to create all of the aspects of the environment and can provide the most valuable information about the future. The education helps students in preparing an essential requirement to deal with change. This article talks about the opportunities and challenges of Islamic education in the future by instilling good mental education for the students as early as possible.